Awareness of side effects of application of HR Analytics - Ankita Gupta (International Journal of Educational Excellence and Innovation, 2025)
The integration of Human Resource (HR) analytics into organizational decision-making has significantly enhanced the ability to manage workforce-related challenges through data-driven insights. However, alongside its numerous benefits, the application of HR analytics also brings potential side effects that may impact employees, organizational culture, and ethical standards. This study explores the level of awareness among HR professionals and organizational stakeholders regarding these side effects, such as privacy concerns, data misuse, employee surveillance, reduced trust, and bias in algorithmic decision-making. By assessing awareness levels, the research aims to highlight the gaps in understanding the ethical and social implications of HR analytics. The findings suggest that while many organizations embrace analytics for strategic gains, awareness of its potential negative consequences remains limited. The study emphasizes the need for transparent policies, ethical guidelines, and continuous training to ensure responsible use of HR analytics that aligns with both organizational goals and employee well-being.